Ascertaining the effects of grass and leaf meals on the gut health and blood indices of broiler chickens – a systematic review - Yee, Lyn Ong; Lim, Eric Teik Chung; Nayan, Nazri; Ngai, Paing Tan; Abdullah Jesse, Faez Firdaus; Sazili, Awis Qurni (Gorgan University of Agricultural Sciences and Natural Resources, 2024)
As the broiler chicken industry continues to develop, antibiotic growth promoters in poultry feed are being phased out because of increasing country restrictions and consumer concerns about food safety. As a result of these bans and efforts to prevent antimicrobial resistance, research into antibiotic alternatives is accelerated to preserve or improve broilers’ production performance. Due to the presence of beneficial compounds like tannins, saponins, flavonoids, and various others found in grass and leaf meals, they possess the potential to substitute antibiotics. This is because secondary metabolites in plant-derived phytobiotics have useful pharmacological qualities that may benefit broilers’ overall production and health. Previous studies, including grass or leaf meals at a dosage of 0.025-20%, have shown several positive effects on gut histomorphology, gut microflora, and blood biochemistry. For instance, lipid profile and liver functions of broiler chickens improved through hypo-cholesterolaemic and hepatoprotective functions of phytocompounds. However, there are also contradictory data and a lack of information on the effect of these plant-based meals on broilers’ blood biomarkers, such as acute phase proteins and heat shock proteins. Therefore, this review provides insight into the potential of grass or leaf meals and their effects on gut health, blood biochemistry, and biomarkers of broiler chickens.